IMPROVING THE STUDENT'S ABILITY TO WRITE PROCEDURE TEXT THROUGH THE MIND MAPPING METHOD IN CLASS XI SMK KARYA NASIONAL KUNINGAN - Santy Nursartka (Indonesian Journal of Education Teaching and Learning (IJETL), 2023)
The purpose of this research to determine the increase in students' ability to write procedure text by applying the mind mapping method. This research is Classroom Action Research (PTK) using the Kemis and Mc Taggart model. The research was carried out at Karya Nasional Kuningan Vocational School on class XI students. The data collected in this research are learning activities in the form of observation sheets and learning achievements in the form of written tests. The research data were analyzed using quantitative descriptive statistics. The results show that the mind mapping method can increase student learning activity, namely in cycle I with an average of 68.86 with learning completeness of 65.71% and the average of student learning activity in cycle II was 77.43 with learning completeness of 82.86%. Based on the findings of the research results above, it can be concluded that applying the mind mapping method can improve skills in writing procedure texts in English lessons.